Erasmus-Erfahrungsberichte. Eine textlinguistische Analyse mit didaktischen Anmerkungen für den DaF-Unterricht - Bies, Andrea (Linguistik Online, 2018)
In this article exchange student testimonials (Erasmus Programme) are examined as text types. In this context function, structure, topics and selected linguistic features of the texts are focused. Analysis shows that the majority of the examined exchange student testimonials demonstrate many common features with advice giving texts. Regarding content, culture comparing topics are found as characteristic elements, and on the linguistic level, a frequent occurrence of elements of conceptual orality. These texts can therefore become relevant authentic teaching materials, as they are able to enhance knowledge of everyday language use and intercultural skills. Thus, the article concludes with didactic notes.